2006
DOI: 10.1002/uog.2694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transvaginal sonography in recumbent and standing maternal positions to predict spontaneous preterm birth in singleton and twin pregnancies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
(36 reference statements)
0
29
2
2
Order By: Relevance
“…Our observations provide evidence that this hypothesis is correct. Gibson 34 In contrast, this was not observed in other studies 34,36,[42][43][44][45][46][47][48] For example, Khalil et al reported serial measurements of cervical length in 209 women with twins at 20-23 weeks and 3-5 weeks later. 46 There were no differences in the predictive value of the first cervical length measurement, the follow-up cervical length measurement, and change in cervical length between the two measurements.…”
Section: Commentmentioning
confidence: 91%
See 3 more Smart Citations
“…Our observations provide evidence that this hypothesis is correct. Gibson 34 In contrast, this was not observed in other studies 34,36,[42][43][44][45][46][47][48] For example, Khalil et al reported serial measurements of cervical length in 209 women with twins at 20-23 weeks and 3-5 weeks later. 46 There were no differences in the predictive value of the first cervical length measurement, the follow-up cervical length measurement, and change in cervical length between the two measurements.…”
Section: Commentmentioning
confidence: 91%
“…The association between a short sonographic cervical length and the risk of subsequent PTB is well-established in singleton 11, 23-28, 52-61 and twin gestations 12,[29][30][31][32][33][34][35][36][37][38][39][40][62][63][64] . Since cervical length changes over time as the time of the onset of labor approaches, we propose that cervical shortening detected with serial sonographic examinations may yield information about the risk of PTB which is not available at the time of the routine sonographic examination in the midtrimester.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of the cervix with the woman in the upright position permits earlier detection of funneling. This may enable earlier and more appropriate intervention to avoid spontaneous preterm birth [41].…”
Section: Funnelingmentioning
confidence: 99%